Analisis Pembiayaan Mudharabah Di BMT Al-Ma’arif Way Kanan Dalam Meningkatkan Pendapatan Pedagang Di Pasar Pagi Kecamatan Baradatu - Anita Fitriani (Falah: Jurnal Hukum Ekonomi Syariah, 2020)
Scientific Journal Entitled "Financing Analysis In Increasing mudharabah Trader's Income in the Morning Market of Baradatu District "this is the result of qualitative field research that aims to address the problem of (1) How to implement financing mudharabah in BMT Al-Ma’arif Kecamatan Baradatu Kabupaten Way Kanan, and (2) How mudharabah credit financing practices in BMT Al-Ma'arif increase the income of traders in the Morning Market in Baradatu District. The research method used is a qualitative approach. Data is collected by interview and documentation. Interviews were conducted with employees and managers of Al-Ma'arif BMT in Baradatu District, Way Kanan Regency and Pasar Pagi traders in Baradatu District who were financing customers using the Mudharabah contract. From the results of this study indicate that the existence of Al-Ma'arif BMT Baradatu Subdistrict, Way Kanan Regency is able to be one of the solutions to various problems faced by the community, especially traders in the Morning Market at Baradatu Sub-District, which is running a business, especially in capital problems that can hamper his efforts. So that with the financing of the mudharabah system provided to the public, especially traders in the Morning Market in Baradatu District who lack capital for their business. Because with the addition of capital, the business has also progressed by increasing the revenue, various sales products and performance. So that with the increase in business production automatically income will also increase. This is indicated that the income of traders who conduct financing has increased with an average percentage increase of 10.39%. Then it can be seen that there is a significant increase in sales turnover and income, this also causes the community and traders especially traders in the Morning Market Baradatu District to be more prosperous and prosperous. Based on the results of this study it is expected that any agency both from BMT Al-Ma'arif Baradatu, Way Kanan Regency and other Islamic financial institutions to be able to maximize products of public interest, such as BMT Al-Ma'arif Baradatu, Way Kanan Regency The Baradatu Subdistrict Branch is able to run well and is able in terms of increasing the income of the community, especially the traders in the Baradatu Subdistrict market, so that later the community or traders who are constrained by capital problems can easily get additional capital for their businesses and increase their incomes.